Motion planning and feedback control for a unicycle in a way point following task: The VFO approach - Michałek, Maciej; Kozłowski, Krzysztof (1951-2021) (Zielona Góra: Uniwersytet Zielonogórski)
This paper is devoted to the "way point following" motion task of a unicycle where the motion planning and the closed-loop motion realization stage are considered. The "way point following" task is determined by the user-defined sequence of waypoints which have to be passed by the unicycle with the assumed finite precision. This sequence will take the vehicle from the initial state to the target state in finite time.
Keywords: unicycle; way point following; motion planning; feedback control; vector fields